Transhumant pastoralism, sustainable management of natural resources and endemic ruminant livestock in the sub-humid zone of West Africa - Ayantunde, Augustine A.; Asse, Rainer; Said, Mohammed Yahya; Fall, Abdou (Springer, 2014)
Transhumant pastoralism is one of the dominant livestock production systems in West Africa, and it is characterized by seasonal and cyclical movement of varying degrees between complementary ecological areas. The common pattern of transhumance is moving herds from areas with pasture and water scarcity such as the Sahelian zone to areas where the forage and water are found, often in the sub-humid zone. Whereas the transhumant herds from the Sahel are mainly Zebu breeds, endemic ruminant livestock (ERL) are the dominant breeds in sub-humid zone of West Africa because of their tolerance to tsetse-borne trypanosomosis disease. These livestock fulfill different functions in the livelihood of rural communities in the region. To identify potential areas of interventions for sustainable natural resource management to improve ERL productivity, a desk study that included spatial mapping was performed to review and document the existing knowledge on transhumance in West Africa. Additionally, group discussions were held to analyze the (actual or potential) effects of transhumant herds on natural resource management and ERL in the sub-humid zone. This study covered sub-humid zone in The Gambia, Guinea, Mali and Senegal. The key question we addressed in this study was as follows: What are the key trends and changes in transhumant pastoralism and how do these impact sustainable management of natural resources including endemic livestock? The results of the desk study and group discussions showed that there have been more southerly movements by transhumant pastoralists into the sub-humid zone over the past three decades and this has contributed to growing competition for grazing resources. The presence of transhumant herds in the sub-humid zone has a potential impact on management and conservation of ERL through crossbreeding with transhumant Zebu breeds from the Sahel but only study sites in Mali showed a high risk.